Relationship of Actinobacillus actinomycetemcomitans serotype b to aggressive periodontitis: Frequency in pure cultured isolates - DOĞAN, BAŞAK (WILEY, 2004)
Background: To our knowledge, the association of the five serotypes of Actinobacillus actinomycetemcomitans (A. actinomycetemcomitans) to the new diagnostic classification scheme defined by the American Academy of Periodontology in 1999 has not yet been described. The goal of this study was to characterize the frequencies of the five serotypes of A. actinomycetemcomitans in A. actinomycetemcomitans isolates from various forms of periodontitis using both old and new diagnostic classifications and to determine the relationships between serotype and age and clinical diagnosis. Methods: A total of 345 A. actinomycetemcomitans isolates from 115 A. actinomycetemcomitans culture-positive subjects (mean age 38.0 +/- 18.3 years, 59% female) were collected. Based on the new classifications, 33 subjects had aggressive periodontitis and 82 chronic periodontitis. According to old classifications, there were six prepubertal periodontitis (PPP), 12 localized juvenile periodontitis (LJP), 15 post-localized juvenile periodontitis (PLJP), 28 refractory periodontitis (Ref-P), and 54 adult periodontitis (AP) cases. Serotypes of A. actinomycetemcomitans were determined by an indirect immunofluorescence assay using serotype-specific polyclonal antisera to A. actinomycetemcomitans strains ATCC 29523, ATCC 43728, ATCC 33384, IDH 781 and IDH 1705 (serotype a, b, c, d, and e, respectively). Proportions of serotype b were examined between different diagnostic and age groups with a Z-test for proportions. Results: Most subjects (n = 100, 86.96%) were infected with a single serotype (22 serotype a, 44 serotype b, 30 serotype c, 1 serotype d, and 3 serotype e). There were 11 subjects (9.57%) with two serotypes and two subjects (1.74%) with 3 serotypes. Two individuals had isolates lacking any detectable serotype antigen. Serotype b was the predominant serotype in children under 18 years of age and young adults between 19 to 35 years, although serotype b status was not significantly associated with age. Serotypes d and e were not found in patients under 35 years old. In 62 adult patients, one subject had serotype d and three had serotype e. Serotype b was the most common serotype in aggressive periodontitis (60.61%). The proportion of cases with serotype b was significantly higher in aggressive periodontitis compared to chronic periodontitis (P = 0.031). Other serotypes were not significantly associated with new diagnostic categories. Serotypes d and e were not detected in aggressive periodontitis. Conclusion: The results of this study show that proportions of serotype b of A. actinomycetemcomitans are significantly greater in culture-positive patients with aggressive periodontitis than those with chronic periodontitis.
Keywords: Actinobacillus actinomycetemcomitans; fluorescence antibody technique, indirect; periodontitis, aggressive/pathogenesis; periodontitis, chronic/pathogenesis; serotyping; BACTERIAL-ENDOCARDITIS; LEUKOTOXIN; STRAINS; INFECTION; DISEASE; GENE; MICROBIOLOGY; GINGIVALIS